2007
DOI: 10.1001/archpsyc.64.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Prenatal Homocysteine Levels as a Risk Factor for Schizophrenia

Abstract: These findings indicate that elevated third-trimester homocysteine levels may be a risk factor for schizophrenia. Elevated third-trimester homocysteine levels may elevate schizophrenia risk through developmental effects on brain structure and function and/or through subtle damage to the placental vasculature that compromises oxygen delivery to the fetus. If future studies both replicate this association and support a causal link, then the use of folic acid supplementation would merit evaluation as a strategy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(97 citation statements)
references
References 62 publications
4
91
1
1
Order By: Relevance
“…Hyperhomocysteinemia did not appear to impact global DNA methylation in leukocytes of patients (Bromberg et al, 2008) or in mice with artificially elevated levels of homocysteine (Bromberg et al, 2011). Archived maternal serum samples assayed for levels of homocysteine during pregnancy indicate that an elevated homocysteine level, particularly during the third trimester, is associated with a greater than twofold increase in risk for SZ (Brown et al, 2007 supplementation has been used in clinical studies of SZ patients to alleviate negative symptoms with somewhat mixed results (Levine et al, 2006;Hill et al, 2011).…”
Section: One Carbon Metabolism and Szmentioning
confidence: 99%
“…Hyperhomocysteinemia did not appear to impact global DNA methylation in leukocytes of patients (Bromberg et al, 2008) or in mice with artificially elevated levels of homocysteine (Bromberg et al, 2011). Archived maternal serum samples assayed for levels of homocysteine during pregnancy indicate that an elevated homocysteine level, particularly during the third trimester, is associated with a greater than twofold increase in risk for SZ (Brown et al, 2007 supplementation has been used in clinical studies of SZ patients to alleviate negative symptoms with somewhat mixed results (Levine et al, 2006;Hill et al, 2011).…”
Section: One Carbon Metabolism and Szmentioning
confidence: 99%
“…There is evidence that deficiencies of folate, vitamin D, iron, and protein during the prenatal period all independently increase the risk of schizophrenia. Homocysteine levels are linked to folate in the metabolic cycle 48 ; and elevated maternal homocysteine levels in the third trimester have been shown to be associated with a 2-fold increase in risk of schizophrenia in the offspring. McGrath and colleagues [49][50][51] have shown that vitamin D supplementation in males in Finland reduced the incidence among these individuals and that both low and high concentrations of neonatal vitamin D are associated with an increase risk of schizophrenia; and a large Danish showed that those exposed to prenatal iron deficiency had a 4-fold increase in risk of schizophrenia.…”
Section: Prenatal Nutritionmentioning
confidence: 99%
“…Homozygosity for this thermolabile mutation causes a deficiency in methylenetetrahydrofolate, with a consequent reduction of the re-methylation of homocysteine to methionine and elevated homocysteine levels. This mutation has been associated with schizophrenia in some but not all studies (111).…”
Section: Amino Acid Disturbances: Glycine Serine and Homocysteinementioning
confidence: 99%
“…Folic acid, cobalamin, and pyridoxine supplementation can markedly lower plasma homocysteine. Thus, if future studies support a causal link, then daily supplementation with these vitamins could prevent clinical deterioration in some patients with schizophrenia and continuation of folic acid supplementation into the second and third trimesters would merit evaluation as a strategy for prevention of schizophrenia in offspring (111).…”
Section: Amino Acid Disturbances: Glycine Serine and Homocysteinementioning
confidence: 99%